2022
DOI: 10.1111/tpj.15935
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome and metabolome analyses identified the mode of sucrose degradation as a metabolic marker for early vegetative propagation in bulbs of Lycoris

Abstract: Vegetative propagation (VP) is an important practice for production in many horticultural plants. Sugar supply constitutes the basis of VP in bulb flowers, but the underlying molecular basis remains elusive. By performing a combined sequencing technologies coupled with ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry approach for metabolic analyses, we compared two Lycoris species with contrasting regeneration rates: high-regeneration Lycoris sprengeri and low-regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 112 publications
1
18
0
Order By: Relevance
“…It has been reported that SUS and IVR mediate sucrose metabolism in plants [ 24 ]. According to the reverse transcription–quantitative polymerase chain reaction (RT–qPCR), NPA treatment significantly increased the expression of genes involved in sucrose metabolism in leaf axils, including LlSusy1 , LlSusy2 , LlCWIN2 , and SOLUBLE ACID INVERTASE ( LlSAI ), which was consistent with the FPKM (fragments per kilobase of exon model per million mapped fragments) value in the transcriptome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that SUS and IVR mediate sucrose metabolism in plants [ 24 ]. According to the reverse transcription–quantitative polymerase chain reaction (RT–qPCR), NPA treatment significantly increased the expression of genes involved in sucrose metabolism in leaf axils, including LlSusy1 , LlSusy2 , LlCWIN2 , and SOLUBLE ACID INVERTASE ( LlSAI ), which was consistent with the FPKM (fragments per kilobase of exon model per million mapped fragments) value in the transcriptome.…”
Section: Resultsmentioning
confidence: 99%
“…Increased expression of genes involved in sucrose metabolism, such as those encoding SUS and IVR pathways, can promote early organogenesis. In the species Gladiolus hybrida and Lycoris , specific genes like GhSUS2 and LsSUS4 facilitate the process of sucrose downloading, leading to an increase in the number of corms and bulblets [ 23 , 24 ]. Furthermore, a class of IVR called cell wall invertase can regulate sucrose transport by the apoplast pathway and promote cell division.…”
Section: Introductionmentioning
confidence: 99%
“…As an energy substance for plant growth and development, sugar involve in plant growth and development as a signaling substance ( Peng et al., 2018 ). Sucrose played a key role in integrating developmental stages and environmental cues to regulate plant yield ( Fernie et al., 2020 ; Liao et al., 2020 ; Wu et al., 2021 ; Ren et al., 2022 ). In this study, the sucrose content was highest in the early stage of stem expansion in lettuce, indicating that it stored a large amount of energy in the early stage for the later stem expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The floral metabolome was detected using ultra-high-performance liquid chromatography (UHLC) as previously described [ 63 ].…”
Section: Methodsmentioning
confidence: 99%